Development of multimedia based on augmented reality to improve students' critical thinking skills - Predian Yudha Prasetya; Sukarmin (Indonesian Journal of Educational Development (IJED), 2026)
Limitations in students' critical thinking skills make it difficult to understand abstract concepts in the chemistry topic of reaction rates, even though critical thinking skills are essential in the twenty-first century. This study aims to develop an Augmented Reality (AR)-based Multimedia that is feasible to use to enhance students' critical thinking skills in the context of the reaction rate topic. Employing a Research & Development (R&D) approach based on the 4D model, the study involved 34 purposively selected twelfth-grade students from State Senior High School 1 Driyorejo. This study used questionnaires, observations, and tests, including validation sheets, student response questionnaires, pre-tests and post-tests, and observation sheets. AR multimedia obtained a mode of 5 in content validity, and construct validity is considered valid. Practicality was confirmed through a student response questionnaire, which scored 91.4%, categorised as practical, and supported by a 99.4% observation score of student activities. Effectiveness was demonstrated by a significant improvement in critical thinking skills, with an overall N-gain score of 0.73 (in the high category) and a Paired Sample T-test p-value of 0.001. Consequently, the developed AR-based multimedia is considered feasible, and teachers are recommended to use it, as it is practical and effective for improving students' critical thinking skills.